RADIASI PLASMA PIJAR KORONA TERHADAP PERTUMBUHAN DAN KANDUNGAN NITROGEN TOTAL BAWANG MERAH DAN BAWANG BOMBAY - Ariyanti, Ariyanti; Prihastanti, Erma; Azam, Much (BIOLINK : Jurnal Biologi Lingkungan Industri Kesehatan, 2020)
Shallots and onions are one of the leading vegetable commodities consumed by the public. The supply of these two onion varieties in Indonesia is not available at all times because is done seasonally. Therefore it is necessary to increase the cultivation, one of which is through the addition of nitrogen through plasma technology. This study to determine the effect of giving plasma nitrogen through plasma technology to the growth of bima onion brebes and grano onions. The study used a Completely Randomized Design (CRD) consisting of 6 treatments with 5 replications. Plasma radiation is carried out on onion seeds and onions with a radiation interval of 15 and 30 minutes. The growth parameters observed were shoot growth time, growth percentage, root length, number of roots, plant height, number of shoots, and nitrogen content. Data were analyzed using ANOVA followed by DMRT Test at 95% confidence level. The results showed that the onion irradiated by plasma for 15 minutes could increase growth and total nitrogen content, while in onions, the highest yield was precisely in the control treatment (0 minute radiation). In onions, plasma administration can inhibit growth and total nitrogen content 0,31%, but can increase the number of roots.